Lightning impulse breakdown voltage RBDPO with the presence of metallic particles under a uniform electric field - Mohd Taufiq Ishak,; Mohd Taufik Jusoh,; Jaafar Adnan,; Rahisham Abd. Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The performance of liquid insulation in power transformer is vulnerable to particles, especially the metallic particles. This paper presents the experimental study on the effect of metallic particles on the palm oil (PO) as dielectric insulating fluid under lightning impulse breakdown voltage. The type of PO used in this study is refined, bleached and deodorized Palm Oil (RBDPO) Olein. Two different types of metallic particles (copper and iron) with different concentrations (clean, low, medium, and high) were studied. The lightning impulse test has been carried out according to IEC 60897 standard and under the influence of a uniform electric field. For the comparative purpose, similar test has been carried out with mineral oil (MO). The presence of metallic particles reduces the average lightning impulse breakdown voltage of MO and PO but shows less significant effect to MO. This is because the streamers in the PO propagate faster and further than in the MO at the same voltage level. Hence, causing the breakdown voltage of PO lower than MO. Under negative lightning impulse, the breakdown voltage of MO is slightly higher than RBDPO. From the study, the increment of the number of particle level contamination will reduce the lightning impulse breakdown voltages of the PO.